Reading Books Differently - Bădulescu, Dana; Cristea, Dan (Knygotyra, 2018)
[full article, abstract in English; abstract in Lithuanian] Starting from the premise that the book is a world in itself, which sometimes invades reality, that the “reality” of the city is “literaturized” in the sense given to it by Bertrand Westphal, and so the city is a book, we present a technology intended to complement electronic reading with contextual information. Automatic language processes working on the original text adorn it with electronic artefacts that highlight mentions of entities and relations between them, thus revealing semantic links within the text and outside it, towards web pages and maps, or helping readers initiate and access communities of people preoccupied with sharing readings. The first instantiation of the “Mapping Books” system allows the reader using a tablet or another mobile device to navigate outside the book, pertaining to the geographical entities that the book contains. “Mapping Books” pushes the interactivity with the book content well beyond the usual hypertext links: a mapped book can contextualise instantaneous positions of the user while reading, as well as her/his personality and cultural preferences. Although rooted in a given, constant text, once associated with a specific reader, the book is personalised to enhance reading satisfaction and maximise guiding. The actual effects of such a technology remain to be studied.